Vaginal Hysterectomy - Sheth, Shirish S; Studd John (New Delhi : Jaypee Brothers Medical Publishers, 2014)
En los últimos años, los avances en las tecnologías laparoscópicas han generado un renovado interés en el abordaje vaginal de la histerectomía, que tiene muchos beneficios comprobados para las pacientes. Este volumen, dedicado a explicar y promover la vía vaginal de la histerectomía, está escrito y editado por un equipo internacional de expertos y proporciona una fuente de información muy necesaria.
In recent years advances in laparoscopic technologies have led to renewed interest in the vaginal approach to hysterectomy, which has many proven benefits for patients. This volume, dedicated to explaining and promoting the vaginal route of hysterectomy, is written and edited by an international team of experts and provides a much-needed source of
Contents 1. The history of vaginal hysterectomy 2. Vaginal hysterectomy : indications and contraindications 3. Preoperative assessment 4. Access to vesicouterine and rectouterina pouches 5. Vaginal hysterectomy for genital prolapse y otros 29 capítulos más 1. Introduction 2. Indications and Contraindications for Non-Descent Vaginal Hysterectomy 3. Preoperative and Peroperative Assessment 4. Anesthetic considerations for Non-Descent Vaginal Hysterectomy (NDVH) 5. Basic Technique for Normal Size Uterus and others chapters more...
Keywords: HISTERECTOMÍA VAGINAL -- CIRUGÍA; VAGINAL HYSTERECTOMY